A Scoping Review of Skin Whitening Products: Users’ Knowledge and Motivations, Marketing Strategies, and Adverse Health Effects - Njoku, Anuli; Sawadogo, Wendemi; Pierce, Taryn; Albert, Kaleigh; Plummer, Fabian (International Platform of Registered Systematic Review and Meta-analysis Protocols, 2025)
Keywords: Adverse effect; Business; Marketing; Medicine; Pharmacology; dept.pch

Moving beyond “risky behavior”: a qualitative interview study exploring geosocial networking app use by sexual minority men and women in the UK and USA - Madden, Hannah; Timpson, Hannah; Breny, Jean; Hope, Vivian; Porcellato, Lorna (International Journal of Sexual Health, 2025)
Objective: Research on use of geosocial networking (GSN) applications (e.g. Grindr, Tinder) by sexual minorities has primarily focused on risky behavior and negative health outcomes (e.g. sexually transmitted infections/HIV, drugs, alcohol, violence) among men who have sex with men. Taking a sex-positive approach, this study aimed to understand how sexual minority GSN app users in the UK and USA perceive impacts on their health and how they manage potential risks. Differences between countries and genders are explored. Design and methods: Qualitative, cross-cultural study in Merseyside (UK) and Connecticut (USA). Photo-elicitation (fake dating profiles) was used in semi-structured interviews conducted with app users seeking same gender partners (n = 31; 15 women, and 16 men) in 2018-2019. Participants were recruited through local LGBTQ+ organizations, social media and from a previous survey, within a quota sampling framework. Transcripts were analyzed using reflexive thematic analysis. Results: Perceived positive health impacts included social and romantic/sexual connections, boosts to self-esteem, and pleasurable sexual experiences. Some negative outcomes were reported, mainly by men, including rejection and low self-esteem, and racism and discrimination. Participants of all genders used strategies to reduce risks to health. Women were particularly cautious of men on apps. No differences between UK and the USA were noted. Conclusions: GSN apps can enable positive sexual experiences and have the potential to increase social cohesion and improve mental wellbeing for stigmatized sexual minorities. All participants took measures to protect both their physical safety and mental wellbeing. Using a sex-positive health promotion approach could empower app users to build on their personal strengths and resources. Although GSN app companies may need to do more to tackle discrimination, apps show a promising opportunity for reducing isolation and health inequities. The similarity of the findings in both areas suggests evidence from the USA may be applicable in the UK.
Keywords: Clinical psychology; Gerontology; Medicine; Psychology; Qualitative research; Sexual behavior; Sexual minority; Sexual orientation; Social psychology; Social science; Sociology; dept.pch

Health behavior and health promotion theories: application in environmental sciences and health - Njoku, Anuli; Molla, Azizur; Tohura, Sharaban (Handbook of Concepts in Health, Health Behavior and Environmental Health, 2025)
Keywords: Environmental health; Health behavior; Health promotion; Medicine; Nursing; Psychology; Public health; dept.pch

From heroes to zeroes: the unraveling support for public health in COVID pandemic-era connecticut - Ketner, Amanda; Micca, Olivia; Barnes, Aaliyah; Ent, Emily; Segala, Shelby; Breny, Jean; DeMaro, Gabriella (Journal of Public Health Management and Practice, 2025)
Keywords: Burnout; Business; Clinical psychology; Coronavirus disease 2019 (COVID-19); Emotional exhaustion; Feeling; Focus group; Health care; Marketing; Medicine; Mental health; Nursing; Pandemic; Personal protective equipment; Political science; Psychiatry; Psychology; Public health; Public relations; Qualitative research; Social psychology; Sociology; Staffing; Thematic analysis; dept.pch

Investigating antecedents of intention to use green agri-food delivery apps: merging TPB with trust and electronic word of mouth - Mouloudj, Kamel; Aprile, Maria; Bouarar, Ahmed; Njoku, Anuli; Evans, Marian; Oanh, Le; Asanza, Dachel; Mouloudj, Smail (Sustainability, 2025)
The rapid expansion of digital platforms has significantly influenced consumer purchasing behaviors, particularly in the agri-food sector. Therefore, this paper investigates the key factors driving customers’ intention to use green agri-food delivery apps (GAFDAs) by integrating trust and electronic word of mouth (eWOM) into the Theory of Planned Behavior (TPB) framework. Additionally, this study examines gender as a moderating variable, assessing whether its influence alters the relationships between key determinants and behavioral intention. Data were collected from 252 Algerian consumers, and the proposed model was tested using SmartPLS 4 and SPSS 26.0. The results confirm that attitude, subjective norms, perceived behavioral control (PBC), trust, and eWOM positively and significantly influence the intention to use GAFDAs, with PBC emerging as the strongest predictor. Moreover, gender moderates the effect of trust on behavioral intention, with trust significantly influencing men’s adoption decisions but not those of females. In contrast, subjective norms and PBC are stronger predictors for female consumers. These findings highlight the importance of gender-specific marketing strategies to enhance GAFDA adoption. This study contributes to the literature by extending TPB with trust, eWOM, and gender moderation, offering valuable insights for marketers, policymakers, and app developers promoting sustainable food consumption.
Keywords: Advertising; Artificial intelligence; Business; Computer science; Control (management); Food delivery; Marketing; Psychology; Theory of planned behavior; Word of mouth; dept.pch

Sleep Duration, Disturbances, and Health-Related Quality of Life in Stroke Survivors - Sawadogo, Wendemi; Adera, Tilahun; Burch, James; Alattar, Maha; Perera, Robert; Howard, Virginia (Archives of Physical Medicine and Rehabilitation, 2025)
Keywords: Insomnia; Odds; Odds ratio; Quality of life; Quality of life (healthcare); Rehabilitation; Sleep (system call); Sleep disturbances; Sleep duration; Stroke (engine); Stroke survivors; dept.pch

Exposure to Endocrine-Disrupting Chemicals and Early Onset of Menarche: A Systematic Review - Njoku, Anuli; Al-Hassan, Mousa; Tohura, Sharaban; Albert, Kaleigh; Pierce, Taryn; Sawadogo, Wendemi (Pollutants, 2025)
There has been a decline in the age at which girls experience menarche worldwide. Research suggests that exposure to endocrine-disrupting chemicals is linked to negative health consequences, including early onset of menarche. This systematic review examined the association between exposure to endocrine-disrupting chemicals (EDCs) and the early onset of menarche. Comprehensive searches of the PubMed, Embase, Web of Science, and Scopus databases were conducted to find relevant studies published from inception to November 2024. Exposure to certain EDCs, such as particulate matter and phthalates, showed significant associations with earlier menarche onset, while exposure to other EDCs (e.g., pyrethroids) was linked to delayed menarche timing. Overall, there were mixed findings in the relationships between various EDC exposures and menarche onset. Few studies investigated how exposure to EDCs and early menarche differed by race and ethnicity. This underscores the need for more studies that examine the relationship between early menarche onset and exposure to endocrine-disrupting substances. Education and policy approaches are also warranted to address this issue.
Keywords: Age of onset; Epidemiology; MEDLINE; Menarche; Risk assessment; Scopus; dept.pch; endocrine-disrupting chemicals; environmental health; menarche; puberty; reproductive health

The Relationship Between Sleep Disorders and Stroke - Sawadogo, Wendemi; Adera, Tilahun (Handbook of the Behavior and Psychology of Disease, 2025)
Stroke is a leading cause of death and disability worldwide. It is a serious disease caused by a disruption of blood flow in the brain resulting from either blockage of blood flow to the brain (ischemic stroke) or sudden bleeding in the brain (hemorrhagic stroke). Stroke survivors experience more sleep disorders than the general population. Sleep disorders could also increase the risk of stroke even in individuals who have no history of stroke. Obstructive sleep apnea and insomnia are the most common sleep disorders associated with increased risk of stroke. Long sleep duration (≥9 h/day) and circadian rhythm changes have also been linked to an increased risk of stroke. This chapter summarizes the current evidence on the relationship between sleep disorders and stroke. © 2025 Springer Nature Switzerland AG.
Keywords: Central sleep apnea; Circadian rhythm disruption; Hypersomnia; Insomnia; Obstructive sleep apnea; Parasomnia; Sleep disorders; Sleep disturbances; Sleep movement disorders; Stroke; dept.pch

Association Between Social Determinants of Health and Borderline Personality Disorder: A Systematic Review - Guerrera, Patrick; Sawadogo, Wendemi; Baviskar, Snehal; Pham, Julie; Patel, Nirali; Cyrus, John (Personality and Mental Health, 2025)
Keywords: Association (psychology); Borderline personality disorder; Context (archaeology); Interpersonal relationship; Mental health; Personality; PsycINFO; Social determinants of health; borderline personality disorder; dept.pch; education; income; social determinants of health; social support; socioeconomic status

WIC Participation During Pregnancy and Low and Very Low Birth Weight by Race and Ethnicity - Sawadogo, Wendemi; McGuire, Neil; Evans, Marian; Tangbe, Praise (Journal of Nutrition Education and Behavior, 2025)
Keywords: Anthropology; Biology; Ethnic group; Gender studies; Low birth weight; Medicine; Obstetrics; Pregnancy; Race (biology); Sociology; WIC; dept.pch; low birth weight; peer-reviewed; pregnancy; race and ethnicity; very low birth weight

Health Information Access Behaviors by Sexual Orientation: A Secondary Data Analysis of the National Health Interview Survey - Gagnon, Kelly; Corey, Stephanie; Gordon, Jacob; Risisky, Deb; Coulter, Robert (Journal of Homosexuality, 2025)
Sexual minority (SM) adults are at increased risk for adverse health outcomes and face unique barriers to engagement and retention in healthcare, including stigma and discrimination. Given known barriers to care, SM adults may prefer online platforms due to limited access to in-person clinical care and fear of discrimination. To date, there is limited knowledge of these behaviors among subgroups of SM adults. This study was a cross-sectional, secondary data analysis of the United States National Health Interview Survey (NHIS) Adult Sample Data Set, 2018. Utilizing descriptive statistics and multivariable logistic regressions, we found that bisexual females had significantly greater odds (AOR = 1.58, CI: 1.04-2.39) of seeking health information online compared to straight females. Similarly, when compared to their straight male counterparts, gay males had significantly higher odds of seeking health information online in the past 12 months (AOR = 2.96, 95% CI: 2.00-4.37). These findings indicate the need for targeting messaging and interventions to address the health concerns of these populations. It also suggests that virtual platforms are viable and perhaps preferred for these subgroups of SM adults. Through continued efforts and research, the field can target relevant health information to populations who need it most by leveraging where they seek it.
Keywords: Environmental health; Health Information National Trends Survey; Health care; Health information; Homosexuality; Medicine; National Health Interview Survey; Orientation (vector space); Political science; Psychology; Reproductive health; Sexual behavior; Sexual minority; Sexual minority health; Sexual orientation; Social psychology; Survey data collection; bisexual women; dept.pch; gay men; health information access; healthcare utilization; online health information; peer-reviewed; public health

Mothers who use opioids and are involved in the criminal justice system: A transformative justice approach - Boeri, Miriam; Lamonica, Aukje; Smith, Sierra (Human Organization, 2025)
Keywords: Criminal justice; Criminology; Developmental psychology; Economic Justice; Law; Political science; Psychology; Restorative justice; Sociology; Theory of criminal justice; Transformative learning; dept.pch; mothers; opioids; recovery; relapse

Insomnia Symptoms, Mental Health Diagnosis, Mental Health Care Utilization, and Perceived Barriers in U.S. Males and Females - Sawadogo, Wendemi; Njoku, Anuli; Jegede, Joy (Journal of Clinical Medicine, 2025)
Objective: We aim to determine the association between insomnia symptoms and mental health in females and males and compare mental health care utilization and perceived barriers between females and males with insomnia symptoms. Methods: This is a cross-sectional study using the National Health Interview Survey. Insomnia symptoms included self-reported “trouble falling asleep”, ‘trouble staying asleep”, and “waking up feeling not well rested”. Mental health included self-reported anxiety and depression. Multivariable logistic regression was used to assess the association between insomnia symptoms and mental health in females and males. Results: A total of 26,691 adults were included. The mean age was 48.2 years; 51.4% were females, and 48.6% were males. Insomnia symptoms were associated with anxiety and depression for both females and males. These associations were stronger in younger adults (<50 years) than older adults (≥50 years). Females with insomnia symptoms were more likely to receive mental health care (OR = 1.7; 95% CI = 1.53, 1.87) but also to delay mental health care because of its cost (OR = 1.96; 95% CI: 1.67, 2.30) or needed mental health care but did not get it because of the cost (OR = 2.14; 95% CI: 1.82, 2.50) than their males counterpart. Conclusions: Insomnia symptoms were associated with mental health in females and males, being stronger in younger adults than older adults, with gender differences in mental health care utilization and financial barriers to mental health care. Holistic approaches involving prevention and better access to mental health care are warranted.
Keywords: Anxiety; Cross-sectional study; Depression (economics); Feeling; Health care; Insomnia; Internal medicine; Logistic regression; Medicine; Mental health; Psychiatry; Psychology; dept.pch; dept.swk; peer-reviewed

Impact of an emergency department take-home naloxone program on subsequent overdose and death - Wills, Brandon; Keyser‐Marcus, Lori; Sawadogo, Wendemi; Gizaw, Andinet; Melmer, Monica; Nguyen, Tammy; Nguyen, Natalie; Davis, Theresa; Ringwood, Katy; Moeller, F. (Heliyon, 2025)
Abstract Background Patients presenting to the emergency department (ED) following nonfatal opioid overdose represent a high-risk population with 5 % of patients dying within a year of the index visit. Objective To evaluate subsequent overdose and death before and after the implementation of an ED discharge naloxone program. Methods This was a retrospective cohort study of ED patients who presented at the Virginia Commonwealth University Health ED with an Opioid Use Disorder (OUD) chief complaint before and after a discharge naloxone program. The pre-naloxone cohort was consecutive ED OUD patients from August 15, 2021, to August 14, 2022, and the post-naloxone cohort from August 15, 2022, to August 14, 2023. The outcomes were subsequent overdose, ED visit to same hospital (VCU), and death within six months of the index visit. Results In total, 1,053 patients were included, of which 529 were in the pre-naloxone cohort and 524 patients in the post-naloxone cohort. The mean age was 44.2 years (SD = 14.0) and 69 % were males. There was a reduction in overdose requiring ED visiting (subsequent ED overdose) and death (4.6 % vs 9.2 % p = 0.03 and 2.0 % vs 5.6 % p = 0.02 respectively) in the post-naloxone cohort compared to the pre-naloxone cohort. After adjusting for sociodemographic and clinical factors, there was a 48 % reduction in the risk of subsequent ED overdose (RR = 0.52, 95 % CI: 0.27, 1.02) and a 63 % reduction in the risk of death (RR = 0.37, 95 % CI: 0.14, 0.95). Conclusion Implementing an ED take-home naloxone program was associated with a reduction in subsequent overdose and death at six months.
Keywords: (+)-Naloxone; Drug overdose; Emergency department; Emergency medicine; Internal medicine; Medical emergency; Medicine; Naloxone; Opioid; Opioid antagonist; Opioid overdose; Poison control; Psychiatry; dept.pch; peer-reviewed

Neighborhood Socioeconomic Status and Breastfeeding Initiation and Duration Among Primiparous Black Women - Griswold, Michele; Crawford, Sybil; Person, Sharina; Rosenberg, Lynn; Palmer, Julie; Cozier, Yvette (Breastfeeding Medicine, 2025)
Background: Social determinants of health account for racial inequities in breastfeeding rates in the United States. There is a gap in the role of neighborhood socioeconomic status (NSES) as it relates to breastfeeding disparities. Methods: Using longitudinal data from the Black Women’s Health Study, we assessed associations of NSES with breastfeeding initiation and duration in a cohort of primiparous U.S. Black women. We also explored associations within strata of important economic indicators, including education, occupation, and marital status. Results: Breastfeeding initiation ( n = 2,705) increased with NSES quartile, from 75.2% in the lowest quartile to 88.3% in the highest quartile ( p < 0.0001). Compared with women living in the highest NSES quartile, those in the lowest quartile had a 41% (odds ratio: 0.59 [95% confidence interval: 0.43, 0.81]) decreased odds of initiating breastfeeding. For breastfeeding duration ( n = 2,172), women residing in NSES quartiles 1–3 were significantly less likely ( p < 0.0001) to breastfeed (44.4%) for 6+ months compared with those living in the highest quartile (62.8%). Adjusted relative risks for those in quartiles 1–3 compared with 4 (highest) were 0.63 (0.45, 0.87), 0.50 (0.37, 0.68), and 0.64 (0.47, 0.86), respectively ( p = 0.0001). There was no statistically significant evidence of effect modification by education, occupation, marital status, and region ( P interaction = >0.05). Conclusion: Living in a lower NSES environment was associated with reduced breastfeeding initiation and duration compared with a higher NSES environment. Research is needed to understand the mechanisms by which neighborhood-level factors influence breastfeeding initiation and duration for Black women in the United States.
Keywords: Black women; Breast feeding; Breastfeeding; Demography; Duration (music); Environmental health; Medicine; Obstetrics; Pediatrics; Population; Socioeconomic status; dept.pch; peer-reviewed

Recent Intimate Partner Violence, Sexual Risk and HIV-Related Worry: Examining the Mediating Effects of Sexual Autonomy - Willie, Tiara; Callands, Tamora; Phillips, Karlye; Flowers, Bianca; Kershaw, Trace (Sexuality Research and Social Policy, 2025)
Keywords: Anxiety; Autonomy; Clinical psychology; Criminology; Domestic violence; Environmental health; HIV; Intimate partner violence; Medicine; Poison control; Political science; Population; Psychiatry; Psychology; Reproductive health; Sexual health; Sexual violence; Suicide prevention; Worry; dept.pch